Cost-effectiveness analysis of cataract surgery with intraocular lens implantation: extracapsular cataract extraction versus phacoemulsification (Faculty of Medicine Universitas Indonesia, 2007)
A randomized single blinded clinical trial to compare the cost-effectiveness of cataract surgery between extracapsular cataract extraction (ECCE) and phacoemulsification (PEA) was conducted at Hospital Universiti Kebangsaan Malaysia (HUKM) from March 2000 until August 2001. The cost of a cataract surgery incurred by hospital, patients and households were calculated preoperatively, one week, two months (for both techniques) and six months (for ECCE only). Effectiveness of cataract surgery was assessed using Visual Function 14 (VF-14), quality of life measurement specifically for vision. The cost analysis results from each 50 subjects of ECCE and PEA group showed that average cost for one ECCE after six months post-operation is USD 458 (± USD 72) and for PEA is USD 528 (± USD 125). VF-14 score showed a significant increased after a week, two months and six months post-operation compared to the score before operation for both techniques (p<0.001). However, there was no significant difference between them (p = 0.225). This study indicated that ECCE is more cost effective compared to PEA with cost per one unit increment of VF-14 score of USD 14 compared to USD 20 for PEA. (Med J Indones 2007; 16:25-31) Keywords: cataract, cost-effectiveness, extracapsular cataract extraction, phacoemulsification, visual function 14